2019
DOI: 10.1002/jac5.1136
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacist patient care services: A systematic review of approaches used for implementation and evaluation

Abstract: Background Studies have identified the positive impact of community pharmacist patient care services. Identifying the most effective implementation strategies and performing robust research are critical to sustaining evidence‐based patient care in this setting. This systematic review aimed to describe: (1) implementation strategies, and (2) dissemination and implementation (D&I) outcomes used to evaluate the implementation of patient care services in community pharmacies. Methods PubMed/MEDLINE, EMBASE, and In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…11 More recently, a review identified strategies used by community pharmacies to implement patient care services, including MTM. 12 While Part D MTM delivery has grown to about 65% of plans utilizing community pharmacists through MTM vendor contracts, there continues to be the need to focus on challenges associated with this delivery. 13 Many PDPs are not utilizing community pharmacists to be the primary provider for Part D MTM services.…”
Section: Introductionmentioning
confidence: 99%
“…11 More recently, a review identified strategies used by community pharmacies to implement patient care services, including MTM. 12 While Part D MTM delivery has grown to about 65% of plans utilizing community pharmacists through MTM vendor contracts, there continues to be the need to focus on challenges associated with this delivery. 13 Many PDPs are not utilizing community pharmacists to be the primary provider for Part D MTM services.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of literature on CPESN networks and the implementation of medication management services within community pharmacies [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Though there is a growing body of literature on these topics, to our knowledge, formally utilizing students as an implementation team for a CPESN network is a novel approach.…”
Section: Discussionmentioning
confidence: 99%
“…There has since been significant growth in pharmacy services in various specialties, with several studies illustrating the increasing responsibilities pharmacists undertake in different patient care settings and their value as part of the interprofessional team. [17][18][19][20][21] With the increase in post-graduate training opportunities, increased certification offerings, and job descriptions which require or prefer post-graduate education, pharmacists who lack this experience may have amplified impostor feelings when considering career changes. Further, fraudulent feelings may emerge when failing to secure post-graduate training or pursuing job opportunities when one may not fulfill all the stated job experience requirements.…”
Section: Evolution Of the Roles And Responsibilities Of Pharmacistsmentioning
confidence: 99%